(untitled) (Contemporary Mathematics, 2022)
The Editor-in-Chief and the publisher have retracted the following article: Zhu Z, Chen J. Numerical Solution to Unsteady One-Dimensional Convection-Diffusion Problems Using Compact Difference Schemes Combined with Runge-Kutta Methods. Contemporary Mathematics. 2021 Nov. 18; 2(4): 399-408. DOI: https://doi.org/10.37256/cm.2420211167. The above article has been retracted as a result of an article with a significant overlap in content having been published in the Universal Journal of Physics Research on November 5, 2021 as: Chen, J., & Zhu, Z. (2021). Compact Difference Schemes Combined with Runge-Kutta Methods for Solving Unsteady Convection-Diffusion Problems. Universal Journal of Physics Research, 1(1), 1-10. DOI: https://doi.org/10.31586/ujpr.2022.155. This decision is made upon our policy on publishing ethics and the COPE guidelines.